The mediating effect of downward influence tactics on the relationship between leadership style and organizational citizenship behavior - Lee, Mi Lian; Low, Guan Tui (Penerbit Universiti Kebangsaan Malaysia, 2012)
This paper examines the effect of leadership styles on employee organizational citizenship behavior (ocB) in Malaysian organizations. Downward influence tactics, as a mediator between leadership and its outcome, is explored to develop the proposed framework. Data from 347 respondents representing several industries show that leaders, who are associated with a transformational leadership style, have a significant positive relationship with their subordinates' OCB. On the contrary, subordinates who perceive their superior as a transactional leader are found to be negatively related with their OCB. Among the downward influence tactics, inspirational appeals and consultation tactics are found to mediate the relationship between transformational leadership and OCB. Thus, a transformational leader may encourage employees' OCB by using a combination of downward influence tactics based on inspirational appeals and the consultation approach. The paper concludes by highlighting the implications of the study for future research and practice.